Proposta de diretrizes para avaliação da segurança de excipientes em formulações pediátricas no Brasil - Dias, Alessandra Paixão (2019)
Childhood is a period of accelerated growth and development, and changes over the time do not happen in a linear or predictable way. The metabolic system shows at different estages of development and maturation, which results in physiological, pharmacokinetic and pharmacodynamic differences in relation to adult population, and to different categories of the pediatric population. Due to the peculiarities, drug’s development for the pediatric population requires attention, particularly with regard to safety. The choice of appropriate excipients is one of the aspects to be considered in the development of pediatric drugs. Besides not being inerts, excipientes may be toxic, and the toxicity may differ among different age groups. The dissertation’s aim is to propose guidelines to evaluate excipients’ safety in drug formulations for pediatric population in Brazil, by developing a guide. For this purpose, it was performed data collection related to excipients’ safety in drugs. The following documents were considered: documents published by Brazilian Health Regulatory Agency (Anvisa); International Council for Harmonisation of Technical Requirements for Pharmaceuticals for Human Use (ICH) guides; documents published by ICH regulatory members. As result, in the internacional scenario, it was noted the importance assigned to excipients’ safety evaluation in drugs intended for pediatric population. In Brazil, regulations regarding clinical research, drug registration and post-approval changes which establish the need to prove the safety of excipients in formulations were identified, but they do not especify how to present the evidence. For some drug categories there is no indication of these requirements in the regulations. It was considered necessary to establish guidelines regarding excipients’ safety assessment, in order to assist Anvisa’s evaluations of drugs intended for pediatric use. Finally, this dissertation presentes, as a product, a guide proposal for excipients’ safety assessment in pediatric formulation in Brazil.